APPLICATION OF THE SINGING METHOD TO IMPROVE ARABIC VOCABULARY MEMORY IN MI DARUSSALAM - Naimah, Mamluatun; Wijaya, Muallim (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The purpose of this study was to find out how the singing method helps students at MI Darussalam retain more Arabic vocabulary. Qualitative research is used in this study. Teachers and students are research subjects. This research can use interviews, observation, and documentation as supporting methods for collecting data. Descriptive analysis can be used for data analysis. In this study, the information checks used were information derivation, information display and final. The results of this study are that most of the learning atmosphere is strong, imaginative, creative, and successful in training. Students are happy and cheerful when the learning process takes place.